Preparation method of boron-doped coated lithium iron manganese phosphate positive electrode material and lithium battery

Through the preparation method of boron-doped coated lithium manganese iron phosphate positive electrode material, the problem of insufficient electrochemical performance and capacity retention rate of lithium manganese iron phosphate is solved, and higher electrochemical performance and structural stability are achieved.

CN119390039AActive Publication Date: 2025-02-07HUNAN YUNENG NEW ENERGY BATTERY MATERIALS CO LTD

Patent Information

Application Number
CN202510008959.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-02-07
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

The electrochemical performance and capacity retention rate of lithium manganese phosphate cannot meet the demand, and poor conductivity and manganese ion dissolution lead to poor charging and discharge rate performance.

Method used

Using boron-doped coated lithium manganese iron phosphate positive electrode material, the complete carbon coating layer is formed and the transmission active site of lithium ions is improved through the pretreatment and sintering process of the first MOF and the second MOF, and the transmission active site of lithium ions is enhanced. Ion conductivity and electrochemical activity.

Benefits of technology

The electrochemical performance, charge and discharge specific capacity and cycle stability of lithium manganese iron phosphate positive electrode material are significantly improved, and structural stability and safety are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390039A_ABST
    Figure CN119390039A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and provides a preparation method of a boron-doped coated lithium iron manganese phosphate positive electrode material and a lithium battery, and the method comprises the following steps: S10, performing first pretreatment based on a lithium source, an iron source, a phosphorus source, a dopant, a dispersant, a first MOF and a solvent to obtain a first precursor; s20, performing first sintering crushing on the first precursor in an inert gas atmosphere to obtain a lithium iron phosphate precursor; s30, performing second pretreatment based on the second MOF, deionized water, a carbon source, a dispersing agent and the lithium iron phosphate precursor to obtain a second precursor; and S40, grinding and drying the second precursor, and carrying out second sintering crushing in an inert gas atmosphere to obtain the lithium iron manganese phosphate positive electrode material. Wherein the first MOF is a boron-based MOF, and the second MOF is a manganese-based MOF. The lithium ion intercalation and deintercalation efficiency is improved, the specific capacity, the cycle capacity retention ratio, the compaction density and the safety of the battery are improved, and the performance of the material is improved from multiple aspects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of lithium batteries, and in particular to a method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material and a lithium battery. Background Art

[0002] Lithium manganese iron phosphate (LiMnFePO4) and lithium iron phosphate (LiFePO4) have similar structures and also have the advantages of stable structure, high capacity, environmental friendliness, high safety, and long cycle life. Compared with lithium iron phosphate, lithium manganese iron phosphate has a higher discharge platform (4.1V) and higher energy density.

[0003] Since the structure of lithium manganese iron phosphate is a hexagonal close-packed structure connected by PO4 tetrahedrons, there is no continuous FeO6 (MnO6) octahedral network, which blocks the lithium ion diffusion channel. Therefore, the lithium ion diffusion rate is relatively low, which in turn causes the poor conductivity of lithium manganese iron phosphate and leads to poor charge and discharge rate performance; in addition, the Mn of lithium manganese iron phosphate 3+ Due to the Jahn-Teller effect at the site, some manganese is dissolved, resulting in unstable capacity retention rate.

[0004] The existing technology has the problem that the electrochemical performance and capacity retention rate of lithium manganese iron phosphate cannot meet the demand. Summary of the invention

[0005] The present application provides a method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material and a lithium battery, which aims to solve the problem of how to improve the electrochemical performance of lithium manganese iron phosphate and improve the capacity retention rate to meet the demand to a certain extent.

[0006] In a first aspect, the present application provides a method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material, comprising: S10, performing a first pretreatment based on a lithium source, an iron source, a phosphorus source, a dopant, a dispersant, a first MOF and a solvent to obtain a first precursor; S20, performing a first sintering and crushing on the first precursor in an inert gas atmosphere to obtain a lithium iron phosphate precursor; S30, performing a second pretreatment based on a second MOF, deionized water, a carbon source, the dispersant, and the lithium iron phosphate precursor to obtain a second precursor; S40, grinding and drying the second precursor, and then performing a second sintering and crushing in an inert gas atmosphere to obtain a lithium manganese iron phosphate positive electrode material; Wherein, the first MOF is a boron-based MOF, and the second MOF is a manganese-based MOF; The first pretreatment includes grinding, ultrasonic stirring, drying and ultraviolet light irradiation; The second pretreatment includes grinding treatment and ultrasonic stirring treatment.

[0007] The present application provides a method for preparing a boron-doped coated lithium iron manganese phosphate positive electrode material. Compared with the prior art, the lithium source, iron source, phosphorus source, dopant, dispersant, first MOF and solvent are subjected to a first pretreatment and then a first sintering, so that the doping element in the dopant can be evenly distributed in the lithium iron phosphate precursor, and the lithium iron phosphate precursor is distributed in the porous and multi-dimensional first MOF with a large specific surface area. After the first sintering, the organic ligands in the first MOF are carbonized to form a complete first carbon coating layer, and the boron in the first MOF is doped in the first carbon coating layer. Boron doping increases the hole carrier concentration of the first carbon coating layer, further improving the conductivity of the carbon layer. Boron doping also increases the number of lithium ion transport active sites, reduces the unit cell parameters, and improves the ion conductivity. Boron doping also improves the electrochemical activity of the lithium iron manganese phosphate positive electrode material, and improves the charge and discharge specific capacity of the lithium iron manganese phosphate positive electrode material, thereby improving the electrochemical performance in many aspects. The second MOF, deionized water, carbon source, dispersant, lithium iron phosphate precursor are subjected to a first pretreatment and then a first sintering is performed. The second pretreatment and the second sintering are performed to further improve the integrity of the lithium iron manganese phosphate coated carbon layer, wherein manganese is doped in the lithium iron phosphate precursor to form a lithium iron manganese phosphate positive electrode material and is redistributed in the porous, multi-dimensional second MOF with a large specific surface area, so that the lithium iron manganese phosphate positive electrode material improves the efficiency of lithium ion insertion and extraction, and improves the specific capacity and cycle stability of the battery; at the same time, the large specific surface area also increases the contact area with the electrolyte, improves the transmission speed of lithium ions, and improves the rate performance of the battery. Since the second MOF is a manganese-based MOF and the manganese ions are magnetic, the binding force between the manganese ions and the manganese-based MOF and the lithium iron phosphate precursor is improved, and the compaction density of the crushed lithium iron manganese phosphate positive electrode material particles is increased, thereby improving the energy density of the lithium iron manganese phosphate positive electrode material, while reducing the dissolution of manganese ions and improving the capacity retention rate; in addition, since the lithium iron manganese phosphate positive electrode material of the present application has a double-layer metal organic framework, the structural stability of the lithium iron manganese phosphate positive electrode material is also improved, and the safety of the lithium iron manganese phosphate positive electrode material is improved.

[0008] In a second aspect, the present application provides a lithium battery, which includes a positive electrode, and the positive electrode includes a lithium iron manganese phosphate positive electrode material obtained by the preparation method of the boron-doped coated lithium iron manganese phosphate positive electrode material as described in any one of the contents of the first aspect.

[0009] The lithium battery of the present application uses a positive electrode made of the lithium iron manganese phosphate positive electrode material obtained by the above-mentioned preparation method. Since the electrochemical properties and compaction density of the lithium iron manganese phosphate positive electrode material are improved in many aspects, the lithium battery has higher energy density, cycle performance and safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0011] Figure 1 It is a schematic flow chart of a method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material provided in one embodiment of the present application; Figure 2 This is a flow chart of obtaining a first precursor by performing a first pretreatment based on a lithium source, an iron source, a phosphorus source, a dopant, a dispersant, a first MOF and a solvent in step S10 provided in an embodiment of the present application; Figure 3 This is a SEM schematic diagram of the lithium manganese iron phosphate positive electrode material of Example 1 of the present application. DETAILED DESCRIPTION

[0012] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0013] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0014] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.

[0015] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0016] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0017] It should be understood that in the various embodiments of the present application, the size of the serial number of each process does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.

[0018] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0019] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0020] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0021] MOF (Metal organic Framework) is the abbreviation of metal-organic framework compounds. It is a crystalline porous material with a periodic network structure formed by the self-assembly of inorganic metal centers (metal ions or metal clusters) and bridging organic ligands. It has both the rigidity of inorganic materials and the flexibility of organic materials, and has a high porosity and surface area.

[0022] Lithium manganese iron phosphate has a similar structure to lithium iron phosphate, and also has the advantages of stable structure, high capacity, environmental friendliness, high safety, long cycle life, etc. Compared with lithium iron phosphate, lithium manganese iron phosphate has a higher discharge platform (4.1V) and higher energy density.

[0023] Since the structure of lithium manganese iron phosphate is a hexagonal close-packed structure connected by PO4 tetrahedrons, there is no continuous FeO6 (MnO6) octahedral network, which blocks the lithium ion diffusion channel. Therefore, the lithium ion diffusion rate is relatively low, which in turn causes the poor conductivity of lithium manganese iron phosphate and leads to poor charge and discharge rate performance; in addition, the nonlinear MnO6 octahedron of lithium manganese iron phosphate has a high conductivity. 3+ The Jahn-Teller effect exists at the site, which causes the dissolution of some manganese, reduces the activity of the lithium manganese iron phosphate positive electrode material, and causes unstable capacity retention rate.

[0024] In order to solve the above problems to a certain extent, Figure 1 As shown, the first aspect of the embodiment of the present application provides a method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material, comprising: S10, performing a first pretreatment based on a lithium source, an iron source, a phosphorus source, a dopant, a dispersant, a first MOF and a solvent to obtain a first precursor; S20, performing a first sintering and crushing on the first precursor in an inert gas atmosphere to obtain a lithium iron phosphate precursor; S30, performing a second pretreatment based on a second MOF, deionized water, a carbon source, a dispersant, and a lithium iron phosphate precursor to obtain a second precursor; S40, grinding and drying the second precursor, and then performing a second sintering and crushing in an inert gas atmosphere to obtain a lithium manganese iron phosphate positive electrode material; Among them, the first MOF is a boron-based MOF, and the second MOF is a manganese-based MOF; The first pretreatment includes grinding, ultrasonic stirring, drying and ultraviolet light irradiation; The second pretreatment includes grinding treatment and ultrasonic stirring treatment.

[0025] The present application provides a method for preparing a boron-doped coated lithium iron manganese phosphate positive electrode material. Compared with the prior art, the lithium source, iron source, phosphorus source, dopant, dispersant, first MOF and solvent are subjected to a first pretreatment and then a first sintering, so that the doping element in the dopant can be evenly distributed in the lithium iron phosphate precursor, and the lithium iron phosphate precursor is distributed in the porous and multi-dimensional first MOF with a large specific surface area. After the first sintering, the organic ligands in the first MOF are carbonized to form a complete first carbon coating layer, and the boron in the first MOF is doped in the first carbon coating layer. Boron doping increases the hole carrier concentration of the first carbon coating layer, further improving the conductivity of the carbon layer. Boron doping also increases the number of lithium ion transport active sites, reduces the unit cell parameters, and improves the ion conductivity. Boron doping also improves the electrochemical activity of the lithium iron manganese phosphate positive electrode material, and improves the charge and discharge specific capacity of the lithium iron manganese phosphate positive electrode material, thereby improving the electrochemical performance in many aspects. The second MOF, deionized water, carbon source, dispersant, lithium iron phosphate precursor are subjected to a first pretreatment and then a first sintering is performed. The second pretreatment and the second sintering are performed to further improve the integrity of the lithium iron manganese phosphate coated carbon layer, wherein manganese is doped in the lithium iron phosphate precursor to form a lithium iron manganese phosphate positive electrode material and is redistributed in the porous, multi-dimensional second MOF with a large specific surface area, so that the lithium iron manganese phosphate positive electrode material improves the efficiency of lithium ion insertion and extraction, and improves the specific capacity and cycle stability of the battery; at the same time, the large specific surface area also increases the contact area with the electrolyte, improves the transmission speed of lithium ions, and improves the rate performance of the battery; and because the second MOF is a manganese-based MOF and the manganese ions are magnetic, the binding force of manganese ions and manganese-based MOFs with the lithium iron phosphate precursor is improved, and the compaction density of the crushed lithium iron manganese phosphate positive electrode material particles is increased, thereby improving the energy density of the lithium iron manganese phosphate positive electrode material, while reducing the dissolution of manganese ions and improving the capacity retention rate; in addition, because the lithium iron manganese phosphate positive electrode material of the present application has a double-layer metal organic framework, the structural stability of the lithium iron manganese phosphate positive electrode material is also improved, and the safety of the lithium iron manganese phosphate positive electrode material is improved. Experimental verification shows that the 0.1C charging specific capacity of the lithium battery made of the lithium iron manganese phosphate positive electrode material prepared in the present application can reach 164.8 mAh / g, and the capacity retention rate of the lithium battery made of the lithium iron manganese phosphate positive electrode material prepared in the present application can reach 97.2%.

[0026] In some embodiments, Figure 2 As shown, step S10 performs a first pretreatment based on a lithium source, an iron source, a phosphorus source, a dopant, a dispersant, a first MOF and a solvent to obtain a first precursor, including: S11, adding a lithium source, an iron source, a phosphorus source, a dopant, and a dispersant into a solvent in a first preset ratio for grinding to obtain a precursor mixture; S12, mixing the precursor mixed liquid and the first MOF according to a second preset ratio and then performing ultrasonic stirring treatment to obtain a precursor MOF mixed liquid; S13, drying the precursor MOF mixed liquid to obtain a precursor MOF mixture; S14, irradiating the precursor MOF mixture with ultraviolet light; S15, grinding the irradiated precursor MOF mixture to obtain a first precursor; The raw materials of the first MOF include boric acid, borohydride nanosheets and a first organic ligand.

[0027] In this embodiment, a lithium source, an iron source, a phosphorus source, a dopant, and a dispersant are added to a solvent in a first preset ratio and mixed, and are mixed with the first MOF in a second preset ratio and dried to obtain a precursor MOF mixture. At this time, the lithium iron phosphate precursor is evenly distributed in the first MOF. Since the first MOF includes boron hydride nanosheets, hydrogen elements are released from the first MOF under the irradiation of ultraviolet light and boron doping is performed, so that the first MOF forms a more loose and porous structure, and the specific surface area of ​​the first MOF is further increased. When the first MOF is subjected to the first sintering with the first precursor (i.e., the lithium iron phosphate precursor) after the volatilization of hydrogen, the contact area between the boron ions in the first MOF and the carbon source after carbonization of the organic ligand and the first precursor is increased, respectively. Boron doping increases the hole carrier concentration of the coated carbon layer, further improves the conductivity of the carbon layer, and while improving the uniformity of boron doping, the coating integrity of the carbon source covering the lithium iron phosphate precursor is also improved, thereby improving the electrochemical performance of the lithium manganese iron phosphate positive electrode material.

[0028] In some embodiments, the carbon content of the lithium iron phosphate precursor is 0.2% to 0.5%; and / or, the mass ratio of the mixture of the boron element and the lithium source, the iron source, the phosphorus source, the dopant, and the dispersant in the first MOF is 1: (10000 to 100000); and / or, the mass ratio of the mixture of the dispersant and the lithium source, the iron source, the phosphorus source, the dopant, and the dispersant is (0.005 to 0.02): 1; and / or, the mass ratio of the mixture of the dopant and the lithium source, the iron source, the phosphorus source, the dopant, and the dispersant is 1 :(10000~100000); and / or, the dopant is one or more of titanium dioxide, magnesium oxide, magnesium hydroxide, niobium pentoxide, vanadium pentoxide, ammonium metavanadate, yttrium oxide, and zirconium oxide; and / or, the molar ratio of the iron element in the iron source: the lithium element in the lithium source: the phosphorus element in the phosphorus source in the first preset ratio is (0.4~0.3): (0.90~1.20): (0.90~1.20); and / or, the volume ratio of the precursor mixture to the second preset ratio of the first MOF is 100: (15~30).

[0029] In this embodiment, if the carbon content of the lithium iron phosphate precursor after carbonization of the organic ligand in the first MOF is lower than the mass ratio range of this embodiment, the carbon layer coated on the lithium iron phosphate precursor will be discontinuous, the material conductivity will be poor, and the electrochemical performance will be poor; if the carbon content is higher than the mass ratio range of this embodiment, the coated carbon layer will be thicker and the coating will be too dense, resulting in increased resistance to lithium ion migration and reduced electrochemical performance; the carbon content of the lithium iron phosphate precursor within the mass ratio range of this embodiment can improve the coating integrity of the carbon layer and improve the electrochemical performance of the lithium manganese iron phosphate positive electrode material. The present embodiment sets a mass ratio range of the boron element and the lithium iron phosphate precursor mixture in the first MOF to avoid excessive or insufficient boron doping in the carbon layer. The boron doping in the carbon layer can better improve the conductivity of the lithium iron manganese phosphate material within the range of the present embodiment. The boron doping amount below the range of the present embodiment will result in a small concentration of hole carriers in the carbon layer, and the conductivity of the carbon layer will not be significantly improved; the boron doping amount above the scope of the present implementation will result in too many defects in the carbon layer, which will destroy the continuity of the carbon layer and is not conducive to improving the electrochemical performance of the material; on the other hand, boron tends to be doped at the phosphorus site, and the boron atomic radius is smaller than the phosphorus atomic radius, and the metallic abundance is stronger than the phosphorus atom. At the same time, the boron oxygen bond energy is stronger than the phosphorus oxygen bond and the bond length is shorter than the phosphorus oxygen bond, so that the volume of the primary particles of the lithium iron phosphate precursor after doping is reduced, and the distance between the ion diffusion channels in the "010" direction is shortened, thereby improving the electrochemical performance of the lithium iron phosphate positive electrode material. The present embodiment also sets the molar ratio of the phosphorus source, the iron source, and the lithium source in step S11, the mass ratio of the dispersant to the feed mixture in step S11, the mass ratio and type of the dopant to the feed mixture, and the second preset ratio of the precursor mixture to the first MOF. The molar ratio range of the phosphorus source, the iron source, and the lithium source based on the present embodiment can better react and avoid incomplete reaction, which affects the pH value of the positive electrode material; based on the mass ratio of the dispersant to the feed mixture, the components can be better dispersed in the solvent, and the solvent is water or ethanol; and the doping ratio of the doping element can be controlled to avoid excessive or insufficient doping elements affecting the electrochemical properties of lithium manganese iron phosphate; the type and mass ratio of the dopant are selected according to the specific needs of the lithium battery to meet the needs of the usage scenario; the volume ratio of the precursor mixture and the second preset ratio of the first MOF in the present embodiment can make the lithium iron phosphate precursor better distributed in the first MOF.

[0030] In some embodiments, the preparation method of the first MOF is: adding boric acid, borohydride nanosheets and a first organic ligand to a solvent according to a first preset dosage ratio, performing a first ultrasonic treatment and performing a solvothermal reaction to obtain a first MOF; wherein the first organic ligand is at least one of a nitrogen-containing ligand or a carboxylic acid ligand. The molar ratio of boric acid and the first organic ligand according to the first preset dosage ratio is 1: (1-5), the mass volume ratio of borohydride to the first MOF solution is 1 mg: (15-30) mL, the parameters of the thermal reaction are: the reaction temperature is 80 ℃~150 ℃, the reaction time is 8 h~30 h; the parameters of the first ultrasonic treatment are: the ultrasonic treatment time is 0.5h~10 h.

[0031] In this embodiment, the boron ions in the boric acid react with the first organic ligand through a solvent thermal reaction so that the first organic ligand and the boron ions undergo a coordination reaction to form a boron-based MOF, and then the first ultrasonic treatment is performed simultaneously, so that the boron hydride nanosheets can be evenly distributed in the boron-based MOF; the thermal reaction parameters and the first ultrasonic treatment parameters of this embodiment can allow the boron ions and the first organic ligand to undergo a more complete coordination reaction, and improve the distribution uniformity of the boron hydride nanosheets; when the first organic ligand adopts a nitrogen-containing ligand, the nitrogen atom in the nitrogen-containing ligand forms a coordination bond with the boron ion, thereby constructing a stable metal organic framework; when the first organic ligand adopts a carboxylic acid ligand, the carboxylate ion forms a coordination bond with the boron ion, and the carboxylic acid ligand also has the effect of hydrogen bonding, which further enhances the stability of the boron-based MOF.

[0032] In some embodiments, the nitrogen-containing ligand includes any one or more of pyridine or pyrazine; The carboxylic acid ligands include any one or more combinations of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, citric acid, phthalic acid, terephthalic acid, isophthalic acid, trimesic acid, and pyromellitic acid; the first organic ligand is determined according to the type of ligand provided in this embodiment, and the molar ratio of the first preset dosage ratio is also determined according to the type of nitrogen-containing ligand or carboxylic acid ligand, which has more choices and is conducive to selection according to specific usage scenario requirements. At the same time, the production cost is reduced due to the diversified sources.

[0033] In some embodiments, the second MOF is a magnetic manganese-based MOF, and the preparation method of the second MOF is: A manganese source and a second organic ligand are added to a solvent according to a second preset dosage ratio, and a second ultrasonic treatment is performed and a solvothermal reaction is performed to obtain a second MOF; wherein the second organic ligand is at least one of a carboxylic acid ligand or an azide ligand; the carboxylic acid ligand includes any one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, citric acid, phthalic acid, terephthalic acid, isophthalic acid, trimesic acid, and pyromellitic acid; the azide ligand includes any one or more of NOTA-azido ligand, tyrosine methyl ester azide ligand, and aromatic amine azide ligand; the molar ratio of the second preset dosage ratio of the manganese source to the second organic ligand is 1: (1-5); the parameters of the thermal reaction are: the reaction temperature is 80 ℃~150 ℃, and the reaction time is 8 h~20 h; the parameters of the second ultrasonic treatment are: the ultrasonic treatment time is 0.5 h ~10 h.

[0034] In this embodiment, since manganese ions are magnetic metal ions, manganese ions and at least one second organic ligand of carboxylic acid ligands or azide ligands undergo a coordination reaction through a solvent thermal reaction to form a stable magnetic manganese-based MOF, which has a strong adsorption capacity for manganese ions and lithium iron phosphate precursors, and then a second ultrasonic treatment is performed to allow manganese ions to be more evenly distributed in the second organic ligand; the ratio of the manganese source to the second organic ligand in this embodiment can allow manganese ions to react completely with the second organic ligand, thereby improving the utilization rate of manganese ions; when the second organic ligand is a carboxylic acid ligand, Manganese ions form coordination bonds with carboxylate ions, and carboxylic acid ligands also have the effect of hydrogen bonding, which further enhances the stability of manganese-based MOF; when the second organic ligand adopts an azide ligand, the manganese ion forms a coordination bond with the azide ion formed by the azide group (-N3); the type of carboxylic acid ligand or azide ligand used in this embodiment has more choices, and the molar ratio of the second preset dosage ratio is also confirmed according to the type of carboxylic acid ligand or azide ligand, which is conducive to selection according to the specific usage scenario requirements, and the production cost is also reduced due to the diversified sources.

[0035] In some embodiments, the second MOF is a hydroxyl-coordinated manganese-based MOF, and the preparation method of the second MOF is: adding a manganese source and a third organic ligand to a solvent in a third preset dosage ratio, performing a third ultrasonic treatment, and performing a solvent thermal reaction at a pH value of 5 to 7 to obtain a second MOF; wherein the third organic ligand is a hydroxyl ligand; the hydroxyl ligand includes a combination of one or more of oxime ligands, ethylene glycol, and propylene glycol; the oxime ligand includes a combination of any one or more of acetaldehyde oxime, dimethyl ketone oxime, cyclohexanone oxime, salicylaldehyde oxime, pyridinealdehyde oxime, butanone oxime, and naphtholaldehyde oxime; the molar ratio of the second preset dosage ratio of the manganese source to the third organic ligand is 1: (1 to 3); the parameters of the thermal reaction are: the reaction temperature is 80°C to 150°C, and the reaction time is 8 h to 20 h; the parameters of the third ultrasonic treatment are: the ultrasonic treatment time is 0.5h to 10 h.

[0036] In the present embodiment, manganese ions and the third organic ligand of the hydroxyl ligand undergo a coordination reaction through a solvothermal reaction to form a hydroxyl-coordinated manganese-based MOF. Since the hydroxyl-coordinated MOF has a higher polarity, it has a stronger adsorption capacity for manganese ions and lithium iron phosphate precursors. A third ultrasonic treatment is then performed to allow the manganese ions to be more evenly distributed in the third organic ligand. The ratio of the manganese source to the third organic ligand in the present embodiment allows the manganese ions to react completely with the third organic ligand, thereby improving the utilization rate of manganese ions. When the third organic ligand is a hydroxyl ligand, the manganese ions form a coordination bond with the hydroxyl group (such as -OH), and the coordination bond formed by the manganese ions and oxygen further enhances the stability of the hydroxyl-coordinated manganese-based MOF. The hydroxyl ligands of the present embodiment provide more choices for the types of ligands, which is conducive to selection according to specific usage scenario requirements. At the same time, the production cost is reduced due to the diversification of sources.

[0037] In some embodiments, the molar ratio of manganese in the second MOF to iron in the iron source is 6-7:4-3; the molar ratio of manganese in the second MOF to iron in the iron source can improve the electrochemical performance of lithium manganese iron phosphate.

[0038] In some embodiments, step S30 is based on the second MOF, deionized water, carbon source, dispersant, lithium iron phosphate precursor to perform a second pretreatment to obtain a second precursor, including: adding deionized water, carbon source, dispersant, lithium iron phosphate precursor to a solvent for grinding treatment to obtain a lithium iron phosphate precursor mixed solution; mixing the lithium iron phosphate precursor mixed solution and the second MOF according to a third preset ratio and then performing ultrasonic stirring treatment to obtain a second precursor; wherein the volume ratio of the third preset ratio of the lithium iron phosphate precursor mixed solution and the second MOF is 100: (10~20); the ultrasonic stirring speed is 150 rpm~300 rpm.

[0039] In this embodiment, the carbon source is the second carbon source, and the first carbon source is the first organic ligand after carbonization in the first MOF; using the volume ratio of the third preset ratio of the lithium iron phosphate precursor mixture and the second MOF in this embodiment can make the first sintered lithium iron phosphate precursor better distributed in the second MOF and prevent the MOF in the second layer from being too thick.

[0040] It should be noted that the magnetic metal ions also include chromium ions, copper ions, cobalt ions, nickel ions, iron ions, and gadolinium ions. In this application, adding other magnetic metal ions to the manganese-based MOF is not restricted, so as to further increase the adsorption force for the lithium iron phosphate precursor, thereby improving the tap density, reducing the dissolution of manganese ions, and improving the capacity retention rate.

[0041] In some embodiments, after the second precursor is ground and dried in step S40, it is subjected to second sintering and crushing in an inert gas atmosphere to obtain a lithium manganese iron phosphate cathode material; wherein, the total carbon content of the lithium manganese iron phosphate cathode material is less than or equal to 0.5%. When grinding the second precursor, large balls and small balls are used to obtain a second precursor with a mixture of a first preset particle size and a second preset particle size; the first preset particle size is 0.6 μm < D501 ≤ 1.5 μm; the second preset particle size is 0.05 μm ≤ D502 ≤ 0.3 μm; in this embodiment, if the carbon content in the lithium manganese iron phosphate cathode material is greater than 0.5%, it will cause the carbon layer coating the lithium iron phosphate precursor to be too thick and the coating to be too dense, resulting in an increase in the migration resistance of lithium ions and a reduction in the electrochemical performance; and because the first preset particle size in the second precursor is larger than the second preset particle size, the second precursor with a small particle size can fully fill the gaps of the second precursor with a large particle size, so the two form a packing density filling with grading, thereby further improving the tap density.

[0042] In some embodiments, the first sintering parameters are: the sintering temperature is 450 °C to 750 °C, and the constant temperature time during sintering is 2 h to 8 h; the second sintering parameters are: the sintering temperature is 650 °C to 750 °C, and the constant temperature time during sintering is 4 h to 8 h. Using the first sintering parameters and the second sintering parameters in this embodiment for sintering can effectively carry out the reduction reaction, carbonize the first MOF to form the first carbon coating and form the second carbon coating for the second carbon source, thereby improving the carbon coating integrity of the lithium manganese iron phosphate cathode material, and further improving the electrochemical performance of the lithium manganese iron phosphate cathode material.

[0043] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium oxalate, lithium carbonate, lithium acetate, lithium phosphate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium chloride and lithium nitrate; and / or, the phosphorus source includes at least one of ammonium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, ferric phosphate, lithium phosphate and lithium dihydrogen phosphate; and / or, the iron source includes at least one of ferrous oxalate, ferrous acetate, ferrous chloride, ferrous sulfate, ferric oxide, ferric phosphate, ferric nitrate, ferric chloride, ferric sulfate, ferric hydroxide, ferric citrate and ferric acetate; and / or, the manganese source is one or more combinations of manganese dihydrogen phosphate, manganese tetraoxide, manganese dioxide, manganese oxide, manganese carbonate; and / or, the inert gas includes any one of nitrogen, argon, or a nitrogen-argon mixture. And / or, the dispersant includes at least one of succinic acid, tripropyl phosphate, dibutyl phosphate, polyamide-based silicone oil, methylcyclosiloxane, sodium dodecylbenzene sulfonate, and sodium octylbenzene sulfonate; and / or, the carbon source is at least one of glucose, sucrose, starch, amino acid, polyethylene glycol, and polyvinylidene fluoride. This embodiment sets the types of lithium source, carbon source, phosphorus source, manganese source, dispersant, and inert gas, providing more types of choices, which is conducive to selection according to specific usage scenario requirements, and also reduces production costs due to the diversification of sources.

[0044] The technical solution of the present application is illustrated below through specific embodiments and comparative examples.

[0045] Example 1 A method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material: Step 1: Preparation of the first MOF: 0.1 mol of boric acid, 0.3 mol of pyridine (the first organic ligand) of a nitrogen-containing ligand and 1 mg of borohydride nanosheets were added to 20 mL of water for a first ultrasonic treatment and a solvothermal reaction to obtain a first MOF solution (i.e., a boron-based MOF); wherein the parameters of the thermal reaction were: reaction temperature of 100 °C and reaction time of 10 h; and the parameters of the first ultrasonic treatment were: ultrasonic treatment time of 2 h.

[0046] Step 2: Prepare the first precursor: Step 2.1, adding 0.4 mol of ferric chloride (iron source), 1.0 mol of lithium carbonate (lithium source), 1.02 mol of phosphoric acid (phosphorus source), titanium dioxide (dopant), and sodium dodecylbenzene sulfonate (dispersant) into water for grinding treatment to obtain a precursor mixture, wherein the mass ratio of titanium dioxide to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 1:50000, and the mass ratio of sodium dodecylbenzene sulfonate to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 0.01:1; Step 2.2, mixing the precursor mixed solution and the first MOF in a second preset volume ratio of 100:30 and then performing ultrasonic stirring to obtain a precursor MOF mixed solution, wherein the mass ratio of the mixture of the boron element in the first MOF and ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 1:10000; Step 2.3, drying the precursor MOF mixed solution to obtain a precursor MOF mixture; Step 2.4, irradiating the precursor MOF mixture with ultraviolet light; Step 2.5, grinding the irradiated precursor MOF mixture to obtain the first precursor (i.e., lithium iron phosphate precursor).

[0047] Step 3: Perform a first sintering and crushing on the first precursor in an inert gas atmosphere of nitrogen to obtain a lithium iron phosphate precursor, wherein the first sintering parameters are: a sintering temperature of 500° C., a constant temperature time of 5 h during sintering, and a carbon content of the lithium iron phosphate precursor of 0.3%.

[0048] Step 4: Preparation of the second MOF: 0.6 mol of manganese carbonate (manganese source) and 1.8 mol of NOTA-Azide (also NOTA-N3, CAS: 2125661-92-7, the second organic ligand) were added to water for a second ultrasonic treatment and a solvothermal reaction to obtain a second MOF; wherein the parameters of the thermal reaction were: reaction temperature of 100 °C, reaction time of 10 h; and the parameters of the second ultrasonic treatment were: ultrasonic treatment time of 3 h.

[0049] Step 5, adding deionized water, glucose (carbon source), sodium dodecylbenzene sulfonate (dispersant), and lithium iron phosphate precursor into water for grinding treatment to obtain a lithium iron phosphate precursor mixed solution; mixing the lithium iron phosphate precursor mixed solution and the second MOF (magnetic manganese-based MOF) at a third preset volume ratio of 100:20, and then performing ultrasonic stirring treatment to obtain a second precursor (i.e., lithium manganese iron phosphate precursor); wherein the ultrasonic stirring speed is 200 rpm, and the molar ratio of manganese in the second MOF to iron in the iron source is 6:4.

[0050] Step 6: Grind the second precursor with large balls and small balls to obtain a second precursor with a mixture of a first preset particle size and a second preset particle size; after drying the second precursor, perform a second sintering and crushing in an inert gas atmosphere of nitrogen to obtain a boron-coated doped lithium iron manganese phosphate cathode material; wherein, the first preset particle size is 0.6 μm < D501 ≤ 1.5 μm; the second preset particle size is 0.05 μm ≤ D502 ≤ 0.3 μm, and the second sintering parameters are: the sintering temperature is 700 °C, the constant temperature time during sintering is 6 h, and the total carbon content of the lithium iron manganese phosphate cathode material is 0.5%.

[0051] Figure 3 SEM schematic diagram of the boron-doped coated lithium iron manganese phosphate cathode material of this embodiment.

[0052] Example 2 The difference from Example 1 is that in Step 1, the first organic ligand is citric acid, a carboxylic acid ligand.

[0053] Example 3 The difference from Example 1 is that in Step 2.2, the volume ratio of the precursor mixture and the first MOF according to the second preset ratio is 100:20, and the mass ratio of the boron element in the first MOF to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzenesulfonate is 1:50000.

[0054] Example 4 The difference from Example 1 is that in Step 2.2, the volume ratio of the precursor mixture and the first MOF according to the second preset ratio is 100:15, and the mass ratio of the boron element in the first MOF to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzenesulfonate is 1:100000.

[0055] Example 5 The difference from Example 1 is that in Step 4, the second organic ligand is glycerol, a hydroxyl ligand.

[0056] Example 6 The difference from Example 1 is that in Step 4, the second organic ligand is citric acid, a carboxylic acid ligand.

[0057] Example 7 The difference from Example 1 is that in Step 5, the volume ratio of the lithium iron phosphate precursor mixture and the second MOF (manganese-based MOF) according to the third preset ratio is 100:15.

[0058] Example 8 The difference from Example 1 is that in Step 5, the volume ratio of the lithium iron phosphate precursor mixture and the second MOF (manganese-based MOF) according to the third preset ratio is 100:10.

[0059] Comparative Example 1 The difference from Example 1 is that no borohydride nanosheets are added in step 1, and ultraviolet light irradiation is not required in step 2.

[0060] Step 1: Preparation of the first MOF: 0.1 mol of boric acid and 0.3 mol of citric acid (the first organic ligand) were added to 20 mL of water for the first ultrasonic treatment and solvent thermal reaction to obtain the first MOF solution (i.e., boron-based MOF); wherein the parameters of the thermal reaction were: reaction temperature of 100 °C, reaction time of 10 h; and the parameters of the first ultrasonic treatment were: ultrasonic treatment time of 2 h.

[0061] Step 2: Prepare the first precursor: Step 2.1, adding 0.4 mol of ferric chloride (iron source), 1.0 mol of lithium carbonate (lithium source), 1.02 mol of phosphoric acid (phosphorus source), titanium dioxide (dopant), and sodium dodecylbenzene sulfonate (dispersant) into water for grinding treatment to obtain a precursor mixture, wherein the mass ratio of titanium dioxide to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 1:50000, and the mass ratio of sodium dodecylbenzene sulfonate to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 0.01:1; Step 2.2, mixing the precursor mixed solution and the first MOF in a second preset volume ratio of 100:30 and then performing ultrasonic stirring to obtain a precursor MOF mixed solution, wherein the mass ratio of the mixture of the boron element in the first MOF and ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 1:10000; Step 2.3, drying the precursor MOF mixed solution to obtain a precursor MOF mixture; Step 2.4, grinding the precursor MOF mixture to obtain a first precursor (i.e., lithium iron phosphate precursor).

[0062] Comparative Example 2 The difference from Example 1 is that the first MOF in step 1 is not prepared, and step 2 is also irrelevant to the first MOF.

[0063] Step 2: Prepare the first precursor: Step 2.1, adding 0.4 mol of ferric chloride (iron source), 1.0 mol of lithium carbonate (lithium source), 1.02 mol of phosphoric acid (phosphorus source), titanium dioxide (dopant), and sodium dodecylbenzene sulfonate (dispersant) into water for grinding treatment to obtain a precursor mixture, wherein the mass ratio of titanium dioxide to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 1:50000, and the mass ratio of sodium dodecylbenzene sulfonate to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzene sulfonate is 0.01:1; Step 2.2, drying the precursor mixture to obtain a precursor mixture; Step 2.5, grinding the precursor mixture to obtain a first precursor (i.e., lithium iron phosphate precursor).

[0064] Comparative Example 3 The difference from Example 1 is that the second MOF in step 4 is not prepared, and step 5 is also irrelevant to the second MOF.

[0065] Step 5: Add deionized water, glucose (carbon source), sodium dodecylbenzene sulfonate (dispersant), and lithium iron phosphate precursor into water for grinding to obtain a lithium iron phosphate precursor mixed solution; subject the lithium iron phosphate precursor mixed solution to ultrasonic stirring to obtain a second precursor (i.e., lithium manganese iron phosphate precursor); wherein the ultrasonic stirring speed is 200 rpm.

[0066] Comparative Example 4 The difference from Example 1 is that the metal ion of the second MOF in step 4 is zinc ion which is a non-magnetic metal ion, and the second organic ligand is terephthalic acid which is a carboxylic acid ligand.

[0067] 0.6 mol of zinc sulfate and 1.8 mol of terephthalic acid (second organic ligand) were added to water for a second ultrasonic treatment and a solvent thermal reaction to obtain a second MOF; wherein the parameters of the thermal reaction were: reaction temperature of 100 °C, reaction time of 10 h; and the parameters of the second ultrasonic treatment were: ultrasonic treatment time of 3 h.

[0068] Comparative Example 5 The difference from Example 1 is that sintering is performed only once.

[0069] Steps 1 and 2 of this embodiment 5 are the same as those of embodiment 1, step 3 of embodiment 1 is cancelled, and steps 4 and 5 of embodiment 1 are steps 3 and 4 of this embodiment.

[0070] Step 5: Grind the mixture of the first precursor and the second precursor using large balls and small balls to obtain the second precursor with a mixture of the first preset particle size and the second preset particle size; after drying the second precursor, perform sintering and crushing in an inert gas atmosphere of nitrogen to obtain a boron-coated doped lithium iron manganese phosphate cathode material; wherein, the first preset particle size is 0.6 μm < D501 ≤ 1.5 μm; the second preset particle size is 0.05 μm ≤ D502 ≤ 0.3 μm, and the sintering parameters are: the sintering temperature is 700 °C, the constant temperature time during sintering is 6 h, and the total carbon content of the lithium iron manganese phosphate cathode material is 0.5%.

[0071] Performance / Data Test: The lithium iron manganese phosphate cathode materials obtained in Examples 1 to 8 and Comparative Examples 1 to 5 were respectively reassembled into coin cells using the same other battery raw materials and conditions, and were subjected to comparative tests under the same conditions.

[0072] Specific surface area: Tested using a JEP V-Sorb2800 device, using the static method, the lithium iron manganese phosphate cathode material sample was pre-treated and dried at 150 °C for 2 h; Use a LAND testing cabinet to perform various electrochemical performance tests on the coin cell, the test temperature is 25 °C, and the test voltage range is set at 2 V - 4.5 V; The specific test data are shown in Table 1.

[0073]

[0074] It can be seen from the data in Table 1 that since the difference between Example 2 and Example 1 is that the first organic ligand is citric acid, a carboxylic acid ligand, and the binding force of the coordination bond between the carboxylate ion and the boron ion is less than the binding force of the coordination bond between the pyridine ring ion and the boron ion, the 0.1C discharge capacity and the 1C discharge capacity both decrease; Since Example 3 is compared with Example 1, the volume ratio of the precursor mixture solution and the first MOF in Example 3 and the mass ratio of the boron element in the first MOF to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzenesulfonate are both less than those in Example 1, and the volume ratio of the precursor mixture solution and the first MOF in Example 4 and the mass ratio of the boron element in the first MOF to the mixture of ferric chloride, lithium carbonate, phosphoric acid, titanium dioxide, and sodium dodecylbenzenesulfonate are both less than those in Example 3, the ratios of the boron ion and the first MOF both decrease, so the 0.1C discharge capacity and the 1C discharge capacity both decrease correspondingly. At the same time, due to the decrease in the ratio of the first MOF, the specific surface area also decreases correspondingly.

[0075] Since the second organic ligand of Example 5 is propylene glycol, which is a hydroxyl ligand, compared with other examples except Example 1, the binding force with manganese ions and lithium iron phosphate precursor is relatively strong, so the capacity retention rate and the compaction density are higher; and the second organic ligand of Example 6 is citric acid, which is a carboxylic acid ligand. Compared with other examples except Example 1, the binding force between carboxylate ions and manganese ions is relatively weak, but the manganese-based carboxylic acid MOF is still a magnetic MOF and has a certain binding force with the lithium iron phosphate precursor, so the capacity retention rate and the compaction density are lower than those of Example 5.

[0076] Since the volume ratio of the lithium iron phosphate precursor mixed solution and the second MOF in Examples 7 and 8 is successively reduced compared with that in Example 1, the 0.1C discharge capacity and the 1C discharge capacity are correspondingly reduced due to the reduction in the content of manganese ions. Since the proportion of the second MOF is reduced, the adsorption force for the lithium iron phosphate precursor is relatively reduced, so the capacity retention rate, compacted density and specific surface area are correspondingly reduced.

[0077] The difference between Comparative Example 1 and Example 1 is that no borohydride nanosheets are added, the boron doping is not uniform, and the boron doping amount is reduced, and the specific surface area of ​​the first MOF is reduced, so the 0.1C discharge capacity, 1C discharge capacity and the specific surface area of ​​the lithium iron manganese phosphate material are correspondingly reduced; Comparative Example 2 does not add the first MOF, and Comparative Example 3 does not add the second MOF. The former has no boron doping and no borohydride to increase the specific surface area of ​​the first MOF, and the latter has no manganese ions to form a lithium iron phosphate positive electrode material, which also reduces the specific surface area. Therefore, the 0.1C discharge capacity, 1C discharge capacity and the specific surface area of ​​the material are correspondingly reduced, and the capacity retention rate of Comparative Example 3 is also correspondingly reduced; the second MOF of Comparative Example 4 is not a magnetic MOF and the second organic ligand is a carboxylic acid ligand, and there is no manganese ion, so the 0.1C discharge capacity, 1C discharge capacity and compaction density are correspondingly reduced; Comparative Example 5 was sintered only once. Since the first MOF was not carbonized in advance, the carbon coating was not complete, so the 0.1C discharge capacity and 1C discharge capacity were correspondingly reduced.

[0078] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described or recorded in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0079] The embodiments described above are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application, and should all be included in the protection scope of the present application.

Claims

1. A method for preparing a boron-doped coated lithium manganese iron phosphate positive electrode material, characterized in that: include: S10, performing a first pretreatment based on a lithium source, an iron source, a phosphorus source, a dopant, a dispersant, a first MOF and a solvent to obtain a first precursor; S20, performing a first sintering and crushing on the first precursor in an inert gas atmosphere to obtain a lithium iron phosphate precursor; S30, performing a second pretreatment based on a second MOF, deionized water, a carbon source, the dispersant, and the lithium iron phosphate precursor to obtain a second precursor; S40, grinding and drying the second precursor, and then performing a second sintering and crushing in an inert gas atmosphere to obtain a lithium manganese iron phosphate positive electrode material; Wherein, the first MOF is a boron-based MOF, and the second MOF is a manganese-based MOF; The first pretreatment includes grinding, ultrasonic stirring, drying and ultraviolet light irradiation; The second pretreatment includes grinding treatment and ultrasonic stirring treatment.

2. The preparation method according to claim 1, characterized in that Step S10 includes: Adding a lithium source, an iron source, a phosphorus source, a dopant, and a dispersant into a solvent in a first preset ratio and grinding the mixture to obtain a precursor mixture; The precursor mixed liquid and the first MOF are mixed in a second preset ratio and then subjected to ultrasonic stirring to obtain a precursor MOF mixed liquid; Drying the precursor MOF mixed solution to obtain a precursor MOF mixture; irradiating the precursor MOF mixture with ultraviolet light; Grinding the irradiated precursor MOF mixture to obtain a first precursor; The raw materials of the first MOF include boric acid, borohydride nanosheets and a first organic ligand.

3. The preparation method according to claim 2, characterized in that: The preparation method of the first MOF is: Adding boric acid, borohydride nanosheets and a first organic ligand into a solvent according to a first preset dosage ratio, performing a first ultrasonic treatment and performing a solvothermal reaction to obtain the first MOF; Wherein, the first organic ligand is at least one of a nitrogen-containing ligand or a carboxylic acid ligand.

4. The preparation method according to claim 3, characterized in that The parameters of the thermal reaction are: reaction temperature is 80°C to 150°C, and reaction time is 10 h to 30 h.

5. The preparation method according to claim 3, characterized in that: The nitrogen-containing ligands include any one or more combinations of pyridine or pyrazine; The carboxylic acid ligands include any one or more combinations of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, citric acid, phthalic acid, terephthalic acid, isophthalic acid, trimesic acid, and pyromellitic acid.

6. The preparation method according to claim 1, characterized in that: The second MOF is a magnetic manganese-based MOF, and the preparation method of the second MOF is: Adding a manganese source and a second organic ligand into a solvent in a second preset dosage ratio, performing a second ultrasonic treatment and performing a solvothermal reaction to obtain the second MOF; Wherein, the second organic ligand is at least one of a carboxylic acid ligand or an azide ligand; The carboxylic acid ligand includes any one or more of oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, citric acid, phthalic acid, terephthalic acid, isophthalic acid, trimesic acid, and pyromellitic acid. The azide ligands include any one or more combinations of NOTA-azide ligands, tyrosine methyl ester azide ligands, and aromatic amine azide ligands.

7. The preparation method according to claim 1, characterized in that: The second MOF is a hydroxyl-coordinated manganese-based MOF, and the preparation method of the second MOF is: Adding a manganese source and a third organic ligand into a solvent according to a third preset dosage ratio, performing a third ultrasonic treatment, and performing a solvothermal reaction at a pH value of 5 to 7 to obtain the second MOF; Wherein, the third organic ligand is a hydroxyl ligand; The hydroxyl ligand includes any one or more combinations of oxime ligands, ethylene glycol, and glycerol; The oxime ligands include any one or more combinations of acetaldehyde oxime, dimethyl ketone oxime, cyclohexanone oxime, salicylaldehyde oxime, pyridinealdehyde oxime, butanone oxime, and naphtholaldehyde oxime.

8. The preparation method according to claim 1, characterized in that: Step S30 includes: Adding deionized water, a carbon source, the dispersant, and the lithium iron phosphate precursor into a solvent for grinding to obtain a lithium iron phosphate precursor mixed solution; The lithium iron phosphate precursor mixed liquid and the second MOF are mixed in a third preset ratio and then subjected to ultrasonic stirring treatment to obtain a second precursor.

9. The preparation method according to claim 1, characterized in that: The molar ratio of manganese in the second MOF to iron in the iron source is 6-7:4-3; and / or, the carbon content of the lithium iron phosphate precursor is 0.2% to 0.5%; And / or, the mass ratio of the mixture of boron element, lithium source, iron source, phosphorus source, dopant and dispersant in the first MOF is 1:(10000-100000); and / or, the mass ratio of the mixture of the dispersant, the lithium source, the iron source, the phosphorus source, the dopant, and the dispersant is (0.005-0.02):1; and / or, the mass ratio of the mixture of the dopant, the lithium source, the iron source, the phosphorus source, the dopant, and the dispersant is 1:(10000-100000); And / or, the dopant is one or more of titanium dioxide, magnesium oxide, magnesium hydroxide, niobium pentoxide, vanadium pentoxide, ammonium metavanadate, yttrium oxide, and zirconium oxide.

10. A lithium battery, characterized in that: The lithium battery comprises a positive electrode, and the positive electrode comprises a lithium iron manganese phosphate positive electrode material obtained by the method for preparing a boron-doped coated lithium iron manganese phosphate positive electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Multi-position co-doped lithium manganese iron phosphate composite material, preparation method and secondary battery

    CN115863623A

  • Preparation method of MOF-derived porous carbon thin layer coated lithium manganese iron phosphate material

    CN116344762A

  • Phosphorus-position boron-doped nanometer disc-shaped lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN116666624A

  • Lithium manganese iron phosphate material, preparation method thereof and lithium battery

    CN117842960A

  • Preparation method of lithium iron phosphate positive electrode material and lithium battery

    CN118373399A

Cited By

  • Preparation method of boronized carbon nitride composite lithium manganese iron phosphate positive electrode material

    CN120854528A

  • Acid pickling modification method of lithium manganese iron phosphate

    CN122079106A